HUBUNGAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET HIPERTENSI: LITERATUR REVIEW - Muhamad Khafid; Dyah Ika Krisnawati; Nety Mawarda Hatmanti; Priyo Mukti Pribadi Winoto (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Hypertension is one of the deadliest diseases worldwide and can affect anyone, especially older adults, whose circulatory system functions decline with age. This literature review aims to examine the relationship between family support and adherence to a hypertension diet. The study design is a literature review using the PECOS format with inclusion-exclusion criteria. The research involved analyzing 6 relevant studies from the last 12 years, using Google Scholar and PubMed databases. The findings show that family support can help people stick to a hypertension diet. In conclusion, a hypertension diet can help reduce iodine consumption, potentially lowering the number of people with hypertension.